Blueprint: Pen Printer / Atasya Syuhada Mohamad, Mohd Haziq Asfa Md Shapari … [et al.] - MOHAMAD, ATASYA SYUHADA; MD SHAPARI, MOHD HAZIQ ASFA; MOHD, NURUL HIDAYATUL AMYRA; UNGKU IBRAHIM, UNGKU AINAA UL-MARDHIAH (2018)
Most tasks and works in our daily life involve processes that using hard copy in order to complete them. The term of 'hard copy' meaning a printed version on paper consisting information in variety of forms such as words and pictures related to the tasks that been done. Hence, tasks or works in the form of hard copy has becoming among our daily life need. Due to this, there is definitely no doubt about the importance in having a printing device specifically design to meet our daily life need. To have a printing device that are light in weight, portable and easy to carry everywhere can be among desired characteristics of an ideal printer. By taking these factors, our company, the Neo Scan Sdn Bhd, had chosen a product that we believe can improve work's efficiency related with printing processes. The product is Pen Printer. This type of product suitable with those having daily works related with the use of hard copy forms such as the students and the office workers